1972
DOI: 10.1111/j.2042-3306.1972.tb03886.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Wound Healing in the Horse

Abstract: SUMMARY Observations on the healing of 2 cm square full thickness cutaneous wounds inflicted on the flanks and lower limbs of Welsh ponies revealed different patterns of wound contraction in the two areas. The rate of healing observed in limb lesions was approximately half that of flank lesions. Stellate scars were produced on the flank which subsequently became further reduced in size. Square scars were produced on the limb which subsequently enlarged in size. The significance of these findings is discussed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…The small number of animals and the differences in age might have influenced the findings. The present study also showed that wounds on the body healed significantly faster than wounds on the limbs, in agreement with earlier clinical and experimental observations (Walton and Neal 1972;Jacobs et al 1984).…”
Section: Discussionsupporting
confidence: 93%
“…The small number of animals and the differences in age might have influenced the findings. The present study also showed that wounds on the body healed significantly faster than wounds on the limbs, in agreement with earlier clinical and experimental observations (Walton and Neal 1972;Jacobs et al 1984).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this experiment confirm observations previously made in other species: the leg wounds of horses heal at a constant speed during the rapid phase of wound closure. [10][11][12][13] The results also demonstrate that the rate of healing is dependent upon the treatment that is applied to the wound. The rate of healing of equine leg wounds (0.56 mm/day) is similar to that reported in limb wounds of humans (0.58 mm/day).s Wounds treated by bandaging or casting following excision of granulation tissue healed at a slower rate than those treated by cryogenic surgery or those left untreated following excision.…”
Section: Discussionmentioning
confidence: 87%
“…Little, however, has been done on the basic mechanics of wound healing from the experimental point of view (Walton and Neal, 1972). Most experimental work has been carried out on pigs, on man and on small laboratory animals (Ordman and Gillman, 1966;Silver, 1971 andWinter andScales, 1963).…”
Section: Department Of Pathology University Of Bristolmentioning
confidence: 99%